Delaying initiation of electroconvulsive treatment after administration of the anaesthetic agent and muscle relaxant reduces the necessity of re-stimulation - Asztalos, Marton; Sartorius, Alexander (Nordic journal of psychiatry, 2018)
Objectives: To investigate the effect of delaying initiation of electroconvulsive therapy (ECT) after administration of anaesthetic agent and muscle relaxant.Methods: A retrospective cohort study utilizing a case-based analysis comparing number of re-stimulations, length of seizures, number of ECTs per series and stimulation dosage before and after introducing a new treatment regimen. In 2013, ECT was initiated approximately 60-90 seconds after administration of thiopental and succinylcholine. This interval was increased to 120 seconds in 2014. Ninety-three patients were included (40 in 2013 and 53 in 2014). Outcome measures were length of seizure, number of re-stimulations, number of ECTs per series and stimulation dosage. Regression model analyses were conducted with entering year of treatment (2013 vs. 2014), sex and age as covariates.Results: We showed that a lowered frequency of re-stimulation was independently associated with the 2014 treatment regimen. No effect of treatment regimen on duration of seizures as measured clinically or by EEG, on number of treatments per series or on stimulation dosage was observed.Conclusions: We found an association between an increased time interval from administration of thiopental and succinylcholine to ECT and a lowered risk of re-stimulations. The current study substantially strengthens the evidence on the benefits of delaying ECT after administration of anaesthetic agent and muscle relaxant.
Gesehen am 04.05.2020